Effects of semi-refined carrageenan (food additive E407a) on cell membranes of leukocytes assessed in vivo and in vitro - Anton Tkachenko; Anatolii Onishchenko; Alexander Roshal; Oksana Nakonechna; Tetyana Chumachenko; Yevgen Posokhov (Medicinski glasnik, 2020)
Aim: To assess the impact of semi-refined carrageenan (E407a) on hydrophobic regions of phosphololipid bilayer in cell membranes of leukocytes collected from rats orally administered this food additive and white blood cells incubated with E407a. Methods: Fluorescent probes (ortho-hydroxy derivatives of 2,5-diaryl-1,3-oxazole) were used to estimate the state of lipid bilayer in leukocytes obtained from rats orally exposed to the food additive E407a and in white blood cells incubated with E407a. Results: No noticeable changes in the physico-chemical properties were observed in the lipid membranes of leukocytes in the region where the probes locate in response to oral intake of semi-refined carrageenan. Incubation of leukocytes with E407a solutions resulted in a decrease in polarity and proton-donor ability of leukocytes in the area of carbonyl groups of phospholipids and in the area of hydrocarbon chains of phospholipids near the polar region of the bilayer. Conclusion: Membrane fluidity abnormalities found in cells exposed to E407a are similar to those observed in patients with IBD suggesting that contribution of carrageenan to IBD development may be partially explained by leukocyte membrane modifications.
Keywords: fluorescence; membrane fluidity; phospholipids; polysaccharides; rats